Lowering the high rate of caesarean delivery in China: an experience from Shanghai. (13th May 2016) - Liu, X; Lynch, CD; Cheng, WW; Landon, MB
Abstract : Objective: To examine the trends of caesarean delivery (CD) after an intervention to lower the high rate of CD at a Chinese maternity hospital. Design: Retrospective cohort study. Setting: A large tertiary obstetric centre in Shanghai, China, from 2007 to 2014. Sample: 81 459 nulliparous women who delivered a term singleton infant. Methods: Logistic regression was used to calculate the odds of CD while adjusting for confounders. Main outcome measure: Rate of CD before and after the intervention. Results: The rate of CD decreased from 51.5% in 2008 to 36.1% in 2014, mostly due to a reduction in non‐indicated antepartum CD from 27.9% in 2010 to 11.9% in 2014. After adjustment, a period effect remained with delivery between 2011 and 2014 associated with a 31% reduction in the odds of CD compared with delivery between 2007 and 2010 [odds ratio (OR): 0.69, 95% CI: 0.66–0.71)] and a 33% reduction in the odds of antepartum CD (OR: 0.67, 95% CI: 0.64–0.69). The frequencies of perinatal mortality (0.5 versus 0.4/1000), hypoxic ischaemic encephalopathy (0.9 versus 1.2/1000), meconium aspiration syndrome (0.5/1000), birth trauma (0.6/1000), respiratory distress syndrome (0.5% versus 0.4%) and necrotising enterocolitis (0.9 versus 0.6/1000) were similar. The frequency of neonatal infection increased slightly (0.6% versus 0.8%), although this could be explained by other factors. Conclusions: A marked reduction in CD has occurred at an urban tertiary care centre as a result of efforts to reduce the high rate of caesarean delivery. No notable differences in neonatal outcomes were observed. Tweetable abstract: High rates of caesarean delivery can be lowered without increases in neonatal morbidity and mortality. Tweetable abstract: High rates of caesarean delivery can be lowered without increases in neonatal morbidity and mortality.